Migrujące pokolenie - oceny życia społecznego kraju własnego i kraju migracji = Migrating Generation - Assesment of the Social Life in a Native Country and Migration Country - Podgórski, Andrzej (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents the results of the research in which the image of social life in Poland and Western European countries in the eyes of young Polish migrants was reconstructed with the application of psychometrics (N=203). This approach assumes that the way people view social reality, in particular phenomena important from the standpoint of personality development (the quality of social bonds, a sense of perspective, opportunity to influence the course of events and shaping their own biographies, choice range of personal patterns), defines the way they function in social space, the life strategies they use, involvement spheres, etc.
Keywords: pokolenie; migracja; ocena jakości życia